2017
DOI: 10.1007/s00223-017-0359-z
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Pathology of a COL1A1 Signal Peptide Heterozygous Mutation Leading to Severe Osteogenesis Imperfecta

Abstract: Osteogenesis imperfecta or “brittle bone disease” is a congenital disorder of connective tissue causing the bone to break easily. Around 85–90% of cases are due to autosomal dominant mutations in the genes encoding type I collagen, the major organic component of bone. Genotype–phenotype correlations have shown that quantitative defects of collagen type I lead to mild OI, whereas structural defects show a wide clinical range from mild to perinatal lethal. This may partially be explained by the type of amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
(16 reference statements)
0
15
0
Order By: Relevance
“…However, the SignalP 4.1 server revealed a marked reduction in the cleavage probability for the Asp15 substitution in FSHR. Efficient cleavage by the signal peptidase requires small and aliphatic residues (in particular Ala, Gly, Ser and Val) at the 1-and 3-positions of the cleavage site (Choo and Ranganathan, 2008;Lindert et al, 2017). Therefore, the Asp15 substitution in FSHR, at the 3-position of the cleavage site, might lead to subcellular mislocalization of FSHR (Bornemann et al, 2008;Chiereghin et al, 2017;Halic et al, 2006;Holtkamp et al, 2012;Rutz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, the SignalP 4.1 server revealed a marked reduction in the cleavage probability for the Asp15 substitution in FSHR. Efficient cleavage by the signal peptidase requires small and aliphatic residues (in particular Ala, Gly, Ser and Val) at the 1-and 3-positions of the cleavage site (Choo and Ranganathan, 2008;Lindert et al, 2017). Therefore, the Asp15 substitution in FSHR, at the 3-position of the cleavage site, might lead to subcellular mislocalization of FSHR (Bornemann et al, 2008;Chiereghin et al, 2017;Halic et al, 2006;Holtkamp et al, 2012;Rutz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts of unaffected individuals of paediatric age were used as controls. Collagen steady‐state analysis in cultured fibroblasts was carried out as previously described . Radioactively labelled and pepsinized procollagens were separated on a 5% SDS‐PAGE and visualized by autoradiography.…”
Section: Methodsmentioning
confidence: 99%
“…Collagen steady-state analysis in cultured fibroblasts was carried out as previously described. 12 Radioactively labelled and pepsinized procollagens were separated on a 5% SDS-PAGE and visualized by autoradiography. Biochemical analysis was conducted prior to genetic analysis in P6 and P7, whereas in P18 it was performed in order to assess the outcome of the COL1A2 p.…”
Section: Collagen Biochemical and Ultrastructural Studymentioning
confidence: 99%
“…We observed that, upon ascorbate (Asc) stimulation of collagen production, collagen-I secretion over a 24 h period was significantly reduced in the heterozygous G425S 1(I)-expressing fibroblasts compared to WT 1(I)-expressing control fibroblasts (Figure 2a; note that in this and other media immunoblots it is not possible to normalize to a 'housekeeping' protein like actin due to the absence of stable markers in media -instead, we carefully ensured equivalent cell counts, media volumes, and timecourses between samples as described in the Materials and Methods). Similar OI-associated collagen-I secretion defects have been observed across many OI genotypes 15,16,[45][46][47][48][49][50][51] . qPCR analysis of mRNA levels showed that classic UPR markers, including HSPA5, DNAJB9, and HYOU1, were not upregulated (Figure 2b) 23 .…”
Section: Global Unfolded Protein Response Activation Exacerbates the Oi Collagen-i Secretion Defect In Fibroblasts Expressing The Col1a1 mentioning
confidence: 69%